Role-Playing Game (RPG) to Increase Student's Learning Motivation - Sholichah, Ana Fatwatush; Gunarhadi, Gunarhadi; Musadad, Akhmad Arif (Journal of Education Technology, 2022)
Online learning during the Covid-19 pandemic made teachers and students study separately and resulting in low student learning enthusiasm. This study aims to create a learning media Role-Playing Game (RPG) to increase student motivation. This research is Research and Development with the Alessi & Trollip model. The population in this study amounted to 512. The sampling technique was a simple random sampling of 120 students. At the alpha test stage, the media was validated by 3 media experts and 3 material experts. After the revision was carried out in the alpha test, the media was beta tested to determine its effectiveness in increasing student learning motivation. The data collection method is quantitative, using a questionnaire instrument and quantitative data analysis using the SPSS 25 program. The results showed that the RPG media created was in the "Very Appropriate" category with an average percentage of 95%. It was concluded that learning using RPG media proved to be more effective than classes that did not use RPG or conventional media, with a score obtained from the statistical test results at a significance level of 0.000 which is less than 0.05 (0.000<0.05). This study implies that teachers need to choose media suitable for learning needs to attract students' enthusiasm for learning.